A RING-FAULT DELINEATION OF AN ANCIENT VOLCANIC CALDERA BASED ON 3-D GRAVITY INVERSE MODELING IN MAJENANG REGION, INDONESIA - Accep Handyarso (KURVATEK, 2022)
Calderas are important geological features in all volcanic environments due to give directives clues of geological resources such as geothermal system, mineralization, or even in oil and gas potential reserved. The ability of recognizing these specific features play an important role in the exploration activities. A good understanding of the geological settings will bring to the right direction and make the exploration activities becomes optimized and cost effective. Gravity method is commonly used for preliminary study almost of any cases due to lightweight, low-cost, and the ability to figure out a wide region quickly. Gravity method has an excellent lateral resolution but it has limitation with the vertical resolution. Applying depth-weighting mechanism makes, the inverse-modeling result becomes interpretable. According to the research, there is a northwest-southeast dextral strike-slip fault in the area, which belongs to the Pamanukan-Cilacap Fault Zone (PCFZ). A Circular anomaly pattern also delineated and interpreted as the ring-fault of an ancient volcanic caldera in the study area. Several high gravity anomaly located within the caldera-rims are interpreted as the lava domes or intrusion rocks. The eruption center point estimated at around the Majenang city. The PCFZ behaves as the weak zones in the area where the magmatism rise through and create the ancient volcano, which now remain as the Majenang Caldera. Keywords: Gravity, Caldera, Ring-Fault, Geological-Resources, Indonesia.